Postmodern wetlands : culture, history, ecology - Giblett, Rodney James (Postmodern theory., 1996)
Postmodern Wetlands explores the representation of wetlands (swamps, marshes, etc.) in western culture. For many, wetlands are a place of disease and horror often associated with the melancholy and the monstrous; in short, they are 'black waters'. Yet, ecologically, wetlands are vitally important for human and other life on earth: they are 'living' waters. The aim of this book is to produce a cultural critique of wetlands as both living and black waters. Drawing on a wide range of disciplines and methodologies, the book analyses wetlands in relation to aesthetics and philosophy, cities and human psychology, mythology and narrative and medical, military, social and conservation history. It discusses these issues using examples across a variety of genres and making reference to British, American and Australian wetlands.